In Search of a Synthesis: Reflections on Two Interpretations of Edvard Radzinskii's Lunin or the Death of Jacques, Recorded in the Presence of the Master - Maia Kipp (Studies in 20th & 21st Century Literature, 1989)
This article examines the contemporary Soviet dramatist Edward Radzinskii's Lunin, the second play in the author's "historical-philosophical trilogy" [Conversations with Socrates (1969), Lunin (1979), and Theater at the Time of Nero and Seneca (1981)]. All three dramas address the relationship between the intellectual and authority. As a philosophical play and as part of the trilogy, Lunin raises universal ethical questions: the banality of power, the paranoia of ideological dogmatists, the fate of the individual who refuses to compromise in the face of a system which will not tolerate any denial of its authority. As an historical play, Lunin is set in a specific historical context. Its protagonist, the Decembrist M.S. Lunin, confronts the Russian autocracy, a tyranny that seeks its legitimacy not in custom or law but in rationality itself and is unchecked by God or man. The composition of this drama and its imagery make it unusually theatrical. The article examines the interpretations of this drama presented in both Soviet and American productions of the play and considers the tension between the philosophical and historical dimensions of the drama evident in these productions. The author concludes that in seeking to exploit the theatrical potential of this play, a production, while taking into account the nature of its audience, should not lose sight of either its philosophical or historical meaning.
Keywords: Edward Radzinskii; Soviet dramatist; Russian drama; Soviet drama; Lunin; historical-philosophical trilogy; Conversations with Socrates; Theatre at the Time of Nero and Seneca; intellectual; authority; relationship; philosphy; Societ productions; American productions; comparative; historical